Simulation and Implementation of Fault Tolerant Controllers for Attitude Control System of Spacecraft Test Bench (2023)
ABSTRACT : The challenging and unpredictable conditions of space present various obstacles to spacecraft operations. To overcome these challenges, spacecraft require resilient systems that can withstand faults and failures. This is where the crucial role of fault-tolerant controllers comes into play, which are developed and implemented to mitigate failures and ensure the continued functionality of spacecraft. This thesis presents the design, validation, and comparison of a fault-tolerant controller applied into spacecraft attitude control system (ACS) by spacecraft test bench implementation. The design process of each controller starts with a literature review, which gives the basis of fault-controller methodologies, and also provides updated information of current used technologies for spacecraft ACSs and test benches. The validation and comparison processes are performed facing two architectures of NLDI controller with the proposed Fuzzy Logic Controller (FLC), in order to evaluate its performance and feasibility of its application in the aerospace industry. Simulation and implementation data are compared using Bland-Altman plot in order to assess the agreement between each set of data, getting a more accurate simulation model for spacecraft attitude controllers design before moving into implementation. Several failure scenarios are conducted to analyze the performance and robustness of each attitude controller. FLC performance shows to be on a par with NLDI controllers, being better in some cases for both nominal and failure scenarios. This demonstrates the capacities that a FLC can have despite that its nature is highly human logic dependent.